2022
DOI: 10.1007/s42330-022-00197-3
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and Structured Inquiry Teaching: Does It Improve Students’ Achievement Motivations in School Science?

Abstract: Guided and open inquiry stands as a valuable instructional strategy for science education. Yet, confirmation and structured inquiry, which provides higher levels of teacher guidance, is more often enacted. These approaches, though more workable, remain unexplored in their effectiveness in improving achievement motivations. This study draws on expectancy-value theory to explore the effect of short-term confirmation and structured inquiry on students’ expectancies of success and intrinsic values in school scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
4
0
2
Order By: Relevance
“…Science education research and curricular reforms promote inquiry as an effective approach to science teaching. Using such a pedagogical approach, students mirror the endeavors of scientists . Lowman-Thomas wrote, “Cultivating curiosity is a great way to improve research skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Science education research and curricular reforms promote inquiry as an effective approach to science teaching. Using such a pedagogical approach, students mirror the endeavors of scientists . Lowman-Thomas wrote, “Cultivating curiosity is a great way to improve research skills.…”
Section: Discussionmentioning
confidence: 99%
“…Using such a pedagogical approach, students mirror the endeavors of scientists. 27 Lowman-Thomas wrote, "Cultivating curiosity is a great way to improve research skills. If students approach the world with interest, a sense of wonder, and a strong drive to learn more, they will be better researchers.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Guided inquiry falls between open-ended inquiry and structured inquiry, where the teacher guides the inquiry process by asking appropriate questions during different phases as in the 5Es learning model (Engage -Explore -Explain -Expand -Evaluate; Bybee, 2014). Studies have indicated the importance of providing support from the teacher during the five stages of learning, allowing learners to explain their understanding, apply concepts in contexts, and assess their knowledge, skills, and abilities (Bybee, 2014;Toma, 2022). Although students have fewer opportunities to plan or conduct their own experiments in this approach, they have more frequent opportunities to draw their own conclusions and interpret their ideas.…”
Section: Inquiry-based Teaching and Learningmentioning
confidence: 99%
“…La enseñanza basada en la indagación desempeña un papel fundamental en la educación científica en todo el mundo, incluyendo España (Morales et al, 2018;Schwartz et al, 2023). Esta difiere de los métodos tradicionales enfocados en la transmisión explícita de conceptos y hechos, ya que promueve un aprendizaje activo que invita al alumnado a explorar y descubrir dichos conceptos mediante prácticas científicas (Aditomo y Klieme, 2020;Alzate y Guevara, 2021;Toma, 2022). La metodología indagatoria pone énfasis en el pensamiento crítico, la resolución de problemas y la experimentación (Akerson y Bartels, 2023;Teig et al, 2022).…”
Section: Introductionunclassified
“…El proyecto busca desarrollar una solución práctica que capacite a los docentes para adoptar eficazmente esta estrategia pedagógica para la enseñanza de las ciencias. El objetivo es proporcionar un recurso que sea fácilmente accesible y que fomente las prácticas de enseñanza y aprendizaje que han ido demandando en las últimas décadas los planes de estudio iberoamericanos en general (Morales et al, 2018;2022), y los españoles en particular (Criado et al, 2014;LOMLOE, 2020). Todo ello, respaldado por la investigación en didáctica de las ciencias (Aguilera y Perales-Palacios, 2020;Lazonder y Harmsen, 2016;Romero-Ariza, 2017;Savelsbergh et al, 2016).…”
Section: Introductionunclassified